Diastereoselective amidoalkylation of (3S,7aR)-6-benzyl-7-hydroxy-3-phenyltetra-hydro-5H-imidazo[1,5-c][1, 3]thiazol-5-one : a short and highly efficient synthesis of (+)-biotin - Chavan, Subhash P.; Chittiboyina, A. G.; Ravindranathan, T.; Kamat, Subhash K.; Kalkote, Uttam R. (Journal of Organic Chemistry, 2005)
A short and highly efficient synthesis of W-biotin in 10 steps with 20% overall yield has been achieved from L-cysteine involving amidoalkylation of hydroxy imidazothiazolone 4 via an acyliminium ion intermediate to furnish C-7-substituted imidazothiazolones 5b as the key step.

Efficient stereoselective synthesis of (2S,4S,5R)-(-)- and (2R,4R,5S)-(+)-bulgecinine - Chavan, Subhash P.; Praveen, C.; Sharma, P.; Kalkote, Uttam R. (Tetrahedron Letters, 2005)
A short synthetic route to (-)-and (+)-bulgecinine, the amino acid moiety of the bulgecins was achieved from the readily available nonchiral pool starting material cis-2-butene-1,4-diol in which a Claisen orthoester rearrangement and a Sharpless asymmetric dihydroxylation were used as the key steps. (C) 2004 Elsevier Ltd. All rights reserved.

New method for the preparation of 1,2-benzisoxazole-3-carboxaldehyde - Kalkote, Uttam R.; Panchgalle, S. R.; Mahakal, K. K.; Choudhary, S. M.; Chavan, Sayalee R. (Journal of Chemical Research, 2005)
Synthesis of 1,2-benzisoxazole-3-carboxaldehyde is achieved from 3-methyl 1,2-benzisoxazole via 3-ethoxymethyl-1,2-benzisoxazole (4).
Keywords: 1; 2-benzisoxazoles; benzylic bromination; indoxazenes

Novel enzymatic route for kinetic resolution of (+/-)1,4-benzodioxan-2-carboxylic acid - Kasture, Sangita M.; Varma, R; Kalkote, Uttam R.; Nene, S; Kulkarni, Bhaskar D. (Biochemical Engineering Journal, 2005)
Ethyl 1,4-benzodioxan-2-carboxylate is used as an intermediate compound for the production of drug doxazosin mesylate. The title compound was kinetically resolved to get S-enantiomer of ethyl 1,4-benzodioxan 2-carboxylate in a simple lipase catalyzed transesterificafion reaction. Ethyl acetate was used as reaction medium as well as acyl donor. The influence of the enzyme source and time of reaction on the enantio selectivity of product were studied. Lipase from Candida antartica-B (Novozyme A/S) catalyzed transesterification reaction with good enantio selectivity towards S-enantiomer. The high enantiomeric ratio, E= 160, provided S-2 an acceptable chemical yield (50%) and enaritiomeric excess (>95%). (c) 2005 Elsevier B.V. All rights reserved.
Keywords: 1; 4-benzodioxan-2-carboxylate; 4-benzodioxan-2-carboxylic acid; doxazosin; enantio selectivity; enantiomeric ratio; ethyl 1; ethyl acetate; Lipases; transesterfication

Simple, concise, stereocontrolled synthesis of (8E,10Z)-pentadecadien-1-ol acetate - Chavan, Subhash P.; Kharul, Rajendra K.; Kamat, Subhash K.; Kalkote, Uttam R.; Kale, R. R. (Synthetic Communications, 2005)
A simple, concise, and stereocontrolled synthesis of (8E, 10Z)-pentadecadien-l -ol acetate involving a Cadiot-Chodkiewicz reaction as the key step is described.
Keywords: acetate; Acrobasis vaccini; Cadiot-Chodkiewicz reaction; diacetylene; Pheromone

Convenient chemoenzymatic synthesis of (1S,7aS)-1-hydroxy-5-oxo-4-(2 `-carboxyethyl)-7a-methyltetrahydro-indane - a key intermediate of steroids - Kalkote, Uttam R.; Purude, A. N.; Puranik, Vedavati G.; Gurjar, M. K. (Journal of Molecular Catalysis B-Enzymatic, 2006)
A porcine pancreatic lipase mediated enzymatic hydrolysis of (+/-)-1-acetoxy-5-oxo-4-(2 `-carbomethoxyethyl)-7a-methyltetrahydroindane (5b) furnished (1S,7aS)-1-acetoxy-5-oxo-4-(2 `-carbomethoxyethyl)-7a-methyltetrahydro-indane (9) and (1R,7aR)-1-hydroxy-5-oxo-4-(2 `-carbomethoxyethyl)-7a-methyltetrahydro-indane (8) with > 99% e.e. which on further chemical hydrolysis gave 1 and ent-1, key intermediates of steroids. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: chemoenzymatic method; Enzymatic hydrolysis; steroids; terpenoids

First enantiospecific synthesis of (-)-parvifoline and (-)-curcuquinone - Chavan, Subhash P.; Thakkar, Mahesh; Jogdand, Ganesh F.; Kalkote, Uttam R. (Journal of Organic Chemistry, 2006)
The first enantiospecific synthesis of (-)-parvifoline, employing ring-closing metathesis as the key step, and (-)-curcuquinone from naturally occurring (R)-(+)-citronellal is described.

Ring closing metathesis approach to the indole alkaloid mitralactonine - Chavan, Subhash P.; Sharma, Pallavi; Sivappa, R.; Kalkote, Uttam R. (Tetrahedron Letters, 2006)
An efficient utilisation of RCM leading to a convenient synthesis of a pentacyclic indole alkaloid is described. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: corynanthe type alkaloid; Dihydroxylation; mitralactonine; RCM; Swern oxidation

Convenient formal synthesis of (+/-)-paroxetine - Chavan, Subhash P.; Khobragade, Dushant A.; Pathak, Ashok B.; Kalkote, Uttam R. (Synthetic Communications, 2007)
A formal total synthesis of antidepressant (+/-)-paroxetine employing a solvent-free Heck reaction is disclosed.
Keywords: antidepressants; carbamate; electrophile; Heck reaction; piperidines

Efficient and practical total synthesis of (+/-)-alpha-cuparenone - Chavan, Subhash P.; Dhawane, Abasaheb N.; Kalkote, Uttam R. (Synthesis-Stuttgart, 2007)
A one-pot cyclopentannulation approach as the key step for the total synthesis of (+/-)-alpha-cuparenone is described.
Keywords: Alkylation; annulation; hydroboration-oxidation; reduction

Facile total synthesis of (+/-)-alpha-cuparenone employing diallylation and RCM as key steps - Chavan, Subhash P.; Dhawane, Abasaheb N.; Kalkote, Uttam R. (Tetrahedron Letter, 2007)
A short and concise total synthesis of alpha-cuparenone employing one-pot diallylation and RCM as the key steps is described. (c) 2006 Elsevier Ltd. All rights reserved.

First enantiospecific synthesis of (-)-heritol: absolute configuration determination - Chavan, Subhash P.; Thakkar, Mahesh; Kalkote, Uttam R. (Tetrahedron Letters, 2007)
The first enantiospecific synthesis of (-)-heritol, from naturally occurring (R)-(+)-citronellal and confirmation of its absolute configuration, is described. (c) 2006 Elsevier Ltd. All rights reserved.

Practical and facile approach towards indole alkaloids: (-)-mitralactonine - Chavan, Subhash P.; Sharma, Pallavi; Sivappa, Rasapalli; Kalkote, Uttam R. (Synlett, 2007)
An efficient approach to (-)-mitralactonine using Pictet-Spengler cyclisation with a highly functionalised masked aldehyde is described. Sharpless asymmetric dihydroxylation (SAD) is utilised to introduce chirality in the key substrate.
Keywords: alkaloids; asymmetric; cyclisations; dihydroxylations; thioacetats

Practical formal synthesis of camptothecin - Chavan, Subhash P.; Pathak, Ashok B.; Kalkote, Uttam R. (Tetrahedron Letter, 2007)
The synthesis of the DE ring of camptothecin using simple and inexpensive starting materials, employing an addition elimination reaction and selective esterification of an aliphatic carboxylic acid as key steps is described. (C) 2007 Elsevier Ltd. All rights reserved.
Keywords: alkaloid; Anticancer; camptothecin; Natural product

Practical synthesis of (+/-)-venlafaxine - Chavan, Subhash P.; Khobragade, Dushant A.; Thakkar, Mahesh; Kalkote, Uttam R. (Synthetic Communications, 2007)
A practical total synthesis of antidepressant (+/-)-venlafaxine is disclosed.
Keywords: antidepressant; Grignard reaction; Michael addition

Short and efficient synthesis of rubrolide E - Chavan, Subhash P.; Pathak, Ashok B.; Pandey, Ankur; Kalkote, Uttam R. (Synthetic Communications, 2007)
Short and efficient synthesis of rubrolide E from commercially available 4-methoxyacetophenone, employing ring-closing metathesis, Knoevenagel condensation, and Reformatsky reactions, are the key steps are described.
Keywords: antibiotics; antitumor; Epoxide; Natural products; Total synthesis

Total synthesis of (+)-camptothecin via an intramolecular palladium-catalyzed cyclization strategy - Chavan, Subhash P.; Pathak, Ashok B.; Kalkote, Uttam R. (Synlett, 2007)
The novel cascade intramolecular Pd-catalyzed cyclization followed by aromatization for the construction Of D ring of (+)-camptothecin as a key step is demonstrated.
Keywords: alkaloids; antitumor; cyclizations; Natural products; Palladium

Total synthesis of pulchellalactam via an RCM strategy - Chavan, Subhash P.; Pathak, Ashok B.; Dhawane, Abasaheb N.; Kalkote, Uttam R. (Synthetic Communications, 2007)
Total synthesis of (Z) pulchellalactam, a CD protein tyrosine phosphatase inhibitor, from commercially available methallyl chloride employing ring-closure metathesis (RCM) as a key step is described.
Keywords: alkaloid; Natural products; pulchellalactam; RCM; Total synthesis

Lipases catalyzed enantioselective hydrolysis of (R,S)-methyl 1,4-benzodioxan-2-carboxylate intermediate for (S)-doxazosin mesylate - Varma, Rita; Kasture, Sangita M.; Nene, Sanjay; Kalkote, Uttam R. (World Journal of Microbiology & Biotechnology, 2008)
(S)-1,4-benzodioxan-2-carboxylic acid-1 is used as starting compound for the production of the more effective (S) enantiomer of the drug doxazosin mesylate. The catalytic ability of some commercial lipases for preparations of (S) enantiomer of 1 from (+/-) methyl 1,4-benzodioxin-2-carboxylate-2 is reported. Lipases from bacterial sources were more successful in resolving the ester than those from the yeast lipases. About 85% enantiomerically pure ester was achieved by lipase from alcaligenes sp.
Keywords: 1; 4-benzodioxan-2-carboxylate; 4-benzodioxan-2-carboxylic acid; doxazosin; Enantioselectivity; Lipases

Tandem aza-michael-condensation-aldol cyclization reaction: approach to the construction of DE synthon of (+/-)-camptothecin - Chavan, Subhash P.; Dhawane, Abasaheb N.; Kalkote, Uttam R. (Synlett, 2008)
An efficient synthesis of the DE ring of camptothecin, employing a Reformatsky and a tandem one-pot, three-step transformation involving aza-Michael reaction, condensation with ethyl malonyl chloride followed by intramolecular `aldol' reaction to furnish the dihydropyridone derivative from commercially available starting materials, has been achieved.
Keywords: Aldol cyclizations; alkaloids; antitumor; Natural products; Reformatsky reaction

Organocatalytic enantioselective synthesis of beta-blockers: (S)-propranolol and (S)-naftopidil - Panchgalle, Sharad P.; Gore, Rohitkumar G.; Chavan, Subhash P.; Kalkote, Uttam R. (Tetrahedron-Asymmetry, 2009)
An efficient enantioselective synthesis of beta-adrenergic blockers (S)-propranolol and (S)-naftopidil with > 98% ee using an L-proline-catalyzed alpha-aminoxylation of an aldehyde as a key step is described. (c) 2009 Elsevier Ltd. All rights reserved.

Studies toward the total synthesis of carba analogue of motif C OF M. TB cell wall AG complex - Gurjar, Mukund K.; Reddy, Challa Nageswar; Kalkote, Uttam R.; Chorghade, Mukund S. (Heterocycles, 2009)
Herein we describe the synthesis of the carba analogue of motif C of arabinogalactan complex present in M tuberculosis cell wall. Pd(0) catalyzed allylic alkylation and Fraser-Reid's glycosidation are the two key reactions that were employed for the synthesis of central glycosyl accepter unit and the glycosylation respectively.
Keywords: Allylic Alkylation; desymmetrization; Fraser-Reid's Glycosidation; M. Tb Ag Complex; Mycobacterium tuberculosis

Enantioselective synthesis of (R)-(+)-alpha-lipoic acid via proline-catalyzed sequential alpha-aminoxylation and HWE olefination of aldehyde - Panchgalle, Sharad P.; Jogdand, Ganesh F.; Chavan, Subhash P.; Kalkote, Uttam R. (Tetrahedron Letters, 2010)
An efficient enantioselective synthesis of (R)-(+)-alpha-lipoic acid is described, in high optical purity (>97% ee), using L-proline-catalyzed sequential alpha-aminoxylation and Horner-Wadsworth-Emmons olefination of aldehyde as the key step. (C) 2010 Elsevier Ltd. All rights reserved.

Formal synthesis of (+/-)-camptothecin via tricyclic lactone as key synthon - Chavan, Subhash P.; Dhawane, Abasaheb N.; Kalkote, Uttam R. (Tetrahedron Letters, 2010)
Formal synthesis of (+/-)-camptothecin via CDE tricyclic lactone employing tandem Michael addition, Dieckmann condensation and addition-elimination reaction as key steps starting from glycinate is described. (C) 2010 Elsevier Ltd. All rights reserved.

Organocatalytic asymmetric synthesis of (-)-delta-coniceine based on sequential proline-catalyzed asymmetric alpha-amination-HWE olefination - Panchgalle, Sharad P.; Bidwai, Harshad B.; Chavan, Subhash P.; Kalkote, Uttam R. (Tetrahedron-Asymmetry, 2010)
An efficient asymmetric synthesis of (-)-delta-coniceine via sequential proline-catalyzed asymmetric alpha-amination and Horner-Wadsworth-Emmons olefination of an aldehyde with excellent enantiomeric excess (>99%) and high yields (overall yield 44%) is described. (C) 2010 Elsevier Ltd. All rights reserved.

Asymmetric total synthesis of (2S,3S)-3-hydroxypipecolic acid - Chavan, Subhash P.; Dumare, Nilesh B.; Harale, Kishor R.; Kalkote, Uttam R. (Tetrahedron Letters, 2011)
A synthetic route to (2S,3S)-3-hydroxypipecolic acid was achieved from readily available nonchiral pool starting material cis-2-butene-1,4-diol and involved Claisen orthoester rearrangement, Sharpless asymmetric dihydroxylation and intramolecular lactamisation of azido lactone as the key steps. (C) 2010 Elsevier Ltd. All rights reserved.

Convenient formal synthesis of (2S,3S)-3-hydroxy pipecolic acid - Chavan, Subhash P.; Harale, Kishor R.; Dumare, Nilesh B.; Kalkote, Uttam R. (Tetrahedron-Asymmetry, 2011)
A convenient synthesis of (2S,3S)-3-hydroxy pipecolic acid starting from inexpensive and easily available L-(+)-tartaric acid has been described. (C) 2011 Elsevier Ltd. All rights reserved.

Exploration of L-proline-catalyzed -aminoxylation of aldehyde to (S)-guaifenesin-related drug molecules - Panchgalle, Sharad P.; Kunte, Sunita S.; Chavan, Subhash P.; Kalkote, Uttam R. (Synthetic Communications, 2011)
[image omitted] An efficient enantioselective synthesis of (S)-guaifenesin with 99% ee using L-proline-catalyzed -aminoxylation of aldehyde as key step is described and explored for asymmetric syntheses of (S)-moprolol and (R)-methocarbamol.
Keywords: -Aminoxylation; guaifenesin; methocarbamol; moprolol; Proline

Highly diastereoselective total synthesis of (+/-)-heritonin and (+/-)-heritol - Chavan, Subhash P.; Garai, Sumanta; Kalkote, Uttam R. (Tetrahedron, 2012)
A highly diastereoselective synthesis of heritol and heritonin by intramolecular cyclization on a preformed sensitive butenolide functionality is described. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Butenolide; cyclization; Dihydroxylation; Friedel-Crafts acylation; Tetralone

Total synthesis of (R)-lipoic acid and (S)-lipoic acid via an Mn (III)-salen-catalyzed oxidative kinetic resolution - Purude, Abhijeet N.; Pawar, Kailash P.; Patil, Niteen B.; Kalkote, Uttam R.; Chavan, Subhash P. (Tetrahedron-Asymmetry, 2015)
The asymmetric synthesis of both the antipodes of alpha-lipoic acid is described. The total synthesis of racemic and asymmetric lipoic acid is achieved from propane 1,3-diol. This work reports the use of Mn (III)-salen-catalyzed oxidative kinetic resolution as the key step to obtain enantiomerically pure (R)- and (S)-lipoic acid. The undesired product formed during the resolution can be recycled to achieve the desired isomer. (C) 2015 Elsevier Ltd. All rights reserved.